IN VITRO ASSESSMENT OF ALCOHOLIC LEAF EXTRACTS OF ANNONA SQUAMOSA AND AEGLE MARMELOS - V.VANITHA; K. J. UMADEVI; K. VIJAYALAKSHMI (The Bioscan, 2010)
Antioxidant potential of leaves of Annona squamosa and Aegle marmelos were studied by using different invitro models like DPPH, ABTS and the scavenging activity was investigated by the production of nitric oxide, hydroxyl radical, super oxides and lipid peroxides. Leaves of Annona squamosa and Aegle marmelos are used in folklore medicine for the treatment of various diseases. It was observed that Annona squamosa (500 μg/mL) showed maximum activity using DPPH where as Aegle marmelos showed maximum scavenging activity using ABTS. Both of them reduced the production of free radicals in a dose dependent manner. This finding shows that the alcoholic leaf extract of Annona squamosa and Aegle marmelos may possess different compounds which have potent antioxidant activity exhibited differently.